2021
DOI: 10.1001/jamanetworkopen.2021.25365
|View full text |Cite
|
Sign up to set email alerts
|

Association of Care Environment With HIV Incidence and Death Among Orphaned, Separated, and Street-Connected Children and Adolescents in Western Kenya

Abstract: Key Points Question What is the association of care environment with incident HIV and death among orphaned, separated, and street-connected children and adolescents in western Kenya? Findings In this cohort study of 2551 orphaned, separated, and street-connected youths in western Kenya, living in an institutional environment was not associated with either death or incident HIV compared with living in a family-based setting. However, living in a street setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
(129 reference statements)
0
17
0
Order By: Relevance
“… 19 Additional details regarding the OSCAR study and its cohort have been previously reported. 15 , 18 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… 19 Additional details regarding the OSCAR study and its cohort have been previously reported. 15 , 18 …”
Section: Methodsmentioning
confidence: 99%
“… 21 The mean age of children entering the model was 10.4 y to align with that of the OSCAR cohort. 15 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, among adolescents (10 to 19 years old), progress is slower, with AIDS-related deaths declining by only 37% over the same period (UNAIDS, 2021). Braitstein et al (2021) observed that living in a street environment versus a family environment was associated with the incidence of HIV and death. Substantial inadequacies with vulnerable young people, extreme poverty, family conflict, child abuse, and neglect are the main reasons why children migrate to the streets and are susceptible to HIV.Current studies highlight that, globally, 1.7 million adolescents are living with HIV in 2019.…”
mentioning
confidence: 99%